Pengaruh Kecukupan Modal terhadap Efisiensi Operasional BMT Alhijrah Bukittinggi 2019-2024: Studi Kasus BMT Alhijrah Bukittinggi - Tiara Puspita Sari; Era Sonita (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
This study is motivated by the continuous increase in initial capital each year that is not followed by a proportional growth in revenue, leading to a decline in operational efficiency. This condition is evident during the 2022–2024 period, where efficiency levels consistently remained below 40%. The issue is presumed to be caused by high operational costs and ineffective capital allocation, resulting in suboptimal revenue generation. These findings indicate weaknesses in capital management strategies and low operational productivity in utilizing available capital. The study employs a quantitative correlational approach and was conducted at BMT Alhijrah Bukittinggi, an Islamic microfinance institution located in Bukittinggi City, West Sumatra. The research utilizes secondary data, including financial and operational reports from the 2022–2023 period, collected through documentation and interviews. Data were analyzed using correlation and linear regression tests to determine the effect of capital adequacy on operational efficiency. The results reveal that capital adequacy has a significant effect on operational efficiency (sig. 0.004 ≤ 0.05). The coefficient of determination (R = 0.547) indicates a moderately strong relationship between capital adequacy and operational efficiency, contributing 49.7% to the performance of BMT Alhijrah Bukittinggi.